New Developments in Christianity in China - Lim, Francis Khek Gee (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The phenomenal expansion of Christianity in China in recent years has attracted much scholarly and public attention. As the country continues to deepen its linkages with the rest of the world, Chinese Christian networks are spreading both within and outside the country. These networks link and crisscross at multiple scales and localities in China while strengthening interactions with overseas Chinese Christians and global Christianity. Many Christian groups throughout the country are harnessing the tremendous potential of new media, such as the internet and mobile apps, to share religious messages, participate in rituals, access information, create online communities, and to evangelize. Chinese Christians have also begun exerting their influence outside China through activities such proselytism, charity work, and development projects. This volume presents cutting edge research by scholars working in the field of Christianity in China, providing valuable insights into how Chinese Christianity is evolving and how it is shaping the country and beyond.